It’s Not a Miscalculation - It’s a Misconception! Uncovering Epistemological Obstacles in Preservice Teachers’ Mathematical Literacy Tasks - Sukma Murni; Febri Restu Widianto; Cucun Sutinah (UIN Siber Syekh Nurjati Cirebon, 2025)
AbstractThis study identified and analyzed epistemological obstacles experienced by prospective elementary school teachers in solving mathematical literacy tasks on plane geometry material. This study employed a case study method, involving 24 students from a university, which was located in Cimahi City, West Java. The diagnostic test served as the research instrument and the data were analyzed using a thematic analysis approach to uncover various epistemological obstacles encountered by undergraduate students, including misconceptions regarding the properties of plane figures and difficulties in applying geometric concepts to mathematical literacy tasks. Epistemological obstacles arise due to the students' inability to connect abstract concepts with practical contexts, as well as their limited understanding of basic geometric concepts. These obstacles primarily stem from misconceptions about fundamental concepts of plane figures, difficulties in applying geometric concepts in contextual situations, and procedural learning approaches that lack conceptual depth. This research contributes to developing geometry learning strategies at the elementary school level, which can ultimately improve the overall quality of mathematics education.Keywords: epistemological obstacle, mathematical literacy, plane geometry. AbstrakPenelitian ini bertujuan untuk mengidentifikasi dan menganalisis hambatan epistemologis yang dialami oleh mahasiswa calon guru sekolah dasar dalam menyelesaikan tugas literasi matematis pada materi geometri bidang datar. Penelitian ini menggunakan metode studi kasus dengan melibatkan 24 mahasiswa dari sebuah universitas yang berlokasi di Kota Cimahi, Jawa Barat. Test diagnostik digunakan sebagai instrument penelitian, dan data dianalisis menggunakan pendekatan analisis tematik untuk mengungkap berbagai hambatan epistemologis yang dialami oleh mahasiswa, termasuk miskonsepsi terhadap sifat-sifat bangun datar dan kesulitan dalam menerapkan konsep geometri pada tugas literasi matematika. Hambatan epistemologis muncul karena ketidakmampuan mahasiswa dalam menghubungkan konsep-konsep abstrak dengan konteks praktis, serta keterbatasan pemahaman terhadap konsep dasar geometri. Hambatan-hambatan ini terutama berasal dari miskonsepsi mengenai konsep dasar bangun datar, kesulitan dalam menerapkan konsep geometri dalam situasi kontekstual, dan pendekatan pembelajaran prosedural yang kurang mendalam secara konseptual. Penelitian ini memberikan kontribusi terhadap pengembangan strategi pembelajaran geometri di tingkat sekolah dasar, yang pada akhirnya dapat meningkatkan kualitas pendidikan matematika secara keseluruhan.Keywords: hambatan epistemis, literasi matematis, bangun datar.